Electrochemical studies of poly (3,4-ethylenedioxythiophene) PEDOT/VS2 nanocomposite as a cathode material for rechargeable lithium batteries - Murugan, A. Vadivel; Gopinath, Chinnakonda S.; Vijayamohanan, K. (Electrochemistry Communications, 2005)
Here, we demonstrate the electrochemical characterization of a new type of layered poly (3,4-ethylenedioxythiophene) PEDOT/ VS2 nanocomposite. It has been prepared via flocculation of delaminated VS2 with subsequent in situ oxidative polymerization of 3,4-ethylenedioxythiophene (EDOT) with VS2 as a host material in the presence of an external oxidizing agent. The interlayer spacing Of VS2 expands from 5.71 to 14.01 A and this interlayer separation is consistent with the existence of a monolayer of PEDOT in the VS2 framework. X-ray diffraction, XPS and TEM studies have been;shown the change in interlayer separation is consistent with the existence of two phases of organic and inorganic species in the nanocomposites corresponding to the intercalation of PEDOT in the VS2 framework. The application potential of the nanocomposite as a cathode material for rechargeable lithium batteries is also demonstrated by the electrochemical intercalation of lithium into the PEDOT/VS2 nanocomposite, where a significant enhancement in the discharge capacity is observed (similar to130 mAh/g) compared to that (80 mAh/g) for pristine VS2. (C) 2004 Published by Elsevier B.V.
Keywords: layered nanocomposite; lithium batteries; polythiophene; vanadium disulfide

Enhancement of double-layer capacitance behavior and its electrical conductivity in layered poly (3, 4-ethylenedioxythiophene)-based nanocomposites - Murugan, A. Vadivel; Viswanath, A. K.; Campet, Guy; Gopinath, Chinnakonda S.; Vijayamohanan, K. (Applied Physics Letters, 2005)
In this letter, we report on the enhanced double-layer capacitance of a layered poly (3, 4-ethylene dioxythiophene) PEDOT-MoO3 nanocomposite, which has been synthesized by a novel microwave irradiation method. The x-ray photoelectron spectroscopy analysis shows the changes in electron density and the shift in binding energy suggesting charge transfer from sulfur atoms upon PEDOT intercalation between MoO3 layers. The room-temperature conductivity for the PEDOT-MoO3 composite is found to be 1.82x10(-1) S cm(-1), which is four orders of magnitude higher than that of the pristine oxide (3.78x10(-5) S cm(-1)). The enhanced double-layer capacitance of the PEDOT-MoO3 nanocomposite (similar to 300 F g(-1)) compared to that (similar to 40 mF g(-1)) of pristine MoO3 is attributed to higher electronic conductivity, enhanced bidimensionality, and increase in surface area of the nanocomposite.

Effect of spacer groups on the performance of MCM-41-supported platinum cluster-derived hydrogenation catalysts - Maity, Niladri; Basu, Susmit; Mapa, Maitri; Rajamohanan, Pattuparambil R.; Ganapathy, Subramanian; Gopinath, Chinnakonda S.; Bhaduri, Sumit; Lahiri, Goutam Kumar (Journal of Catalysis, 2006)
MCM-41 was functionalized with (EtO)(3)SiCH2Cl, (MeO)(3)SiCH2CH2CH2Cl, and (CH3)Cl2SiCH2Cl. The functionalized materials were characterized by solid-state NMR (CPMAS, Si-29 and C-13) and XPS. The NMR data indicate that three new silicon environments were created by(EtO)(3)SiCH2Cl and (MeO)(3)SiCH2CH2CH2Cl, whereas with (CH3)Cl2SiCH2Cl, two new silicon environments were obtained. XPS results from Si 2p core level and the valence band from the material functionalized by (MeO)(3)Si(CH2)(3)Cl was found to be the same as that of the corresponding fresh catalyst (1a), in contrast to that of the materials functionalized by the other two silane reagents. After further functionalization with triethylamine, these materials were used as inorganic anion exchangers to support the cluster anion [Pt-12(CO)(24)](2-). Solid-state NMR (29Si, C-13, N-15) was used to establish the presence of the quaternary ammonium group in the cluster-supported species. Analogous materials were also created using fumed silica as the support, and all of the cluster-supported materials were tested as catalysts for the hydrogenation of methyl pyruvate, acetophenone, nitrobenzene, benzonitrile, ethylacetoacetate, 4-nitrotoluene, cyclohexanone, allyl alcohol, and styrene. The best activity was obtained for the catalyst that had MCM-41 as the support and chloropropyl as the spacer group. TEM showed that the supports and the spacer groups had observable effects on the platinum crystallite size of the catalysts. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: functionalized inorganic oxides; hydrogenation catalysts; MCM-41; platinum carbonyl cluster; Solid-state NMR; spacer groups; XPS

Exfoliation-induced nanoribbon formation of poly(3,4-ethylene dioxythiophene) PEDOT between MoS2 layers as cathode material for lithium batteries - Murugan, A. Vadivel; Quintin, M.; Delville, M. H.; Campet, Guy; Gopinath, Chinnakonda S.; Vijayamohanan, K. (Journal of Power Sources, 2006)
A new type of layered nanocomposite synthesized by delaminated MoS2 nanosheets and poly(3,4-ethylenedioxythiophene) (PEDOT) are restacked to produce alternate polymer nanoribbons between layers Of MoS2 with an interlayer distance of similar to 1.38 nm. The unique properties of resulting nanocomposite are investigated by powder XRD, XPS, SEM, TEM, and four-probe conductivity measurements. The obtained nanocomposite can be used as a cathode material for a small power rechargeable lithium battery as demonstrated by the electrochemical insertion of lithium into the PEDOT/MoS2 nanocomposite. A significant enhancement in the discharge capacity (100 mAh g(-1)) is observed compared with that (40 mAh g(-1)) for MoS2. (c) 2005 Elsevier B.V All rights reserved.
Keywords: cathode material; lithium batteries; MoS2; organic-inorganic nanocomposite; PEDOT-nanoribbons

Electrochromic device (ECD) cell characterization on electron beam evaporated MoO3 films by intercalating/deintercalating the H+ ions - Sivakumar, R.; Gopinath, Chinnakonda S.; Jayachandran, M.; Sanjeeviraja, C. (Current Applied Physics, 2007)
Thin films of molybdenum oxide (MoO3) is one of the most interesting layered intercalation materials because of its excellent application in solid state batteries, large-area window and display systems. In recent years there has been considerable interest in variable transmittance electrochromic devices (ECD) based on Li+, H+ and K+ intercalation in transition metal oxide (MoO3) thin films. In the present investigation, thin films of MoO3 were prepared by electron beam evaporation technique on microscopic glass and fluorine doped tin oxide (FTO) coated glass substrates for the application in electrochromic device cells. The compositional stoichiometry of the films was studied by X-ray photoelectron spectroscopy (XPS). The electrochromic nature of the films has been analyzed by inserting H+ ions from the H2SO4 electrolyte solution using the cyclic-voltammetry (CV) technique. We studied the electrochromic device cells (ECD) incorporating an evaporated MoO3 thin films as electrochromic layers. The devices exhibit good optical properties with low transmittance values in the colored state, which make them suitable for large-area window applications. The maximum coloration efficiency of the cell was observed at about 70 cm(2)/c. (c) 2005 Published by Elsevier B.V.
Keywords: coloration efficiency; electrochromic device cells; molybdenum oxide thin films; optical density; stoichiometry

Effect of fuel and its concentration on the nature of Mn in Mn/CeO2 solid solutions prepared by solution combustion synthesis - Murugan, B.; Ramaswamy, A. V.; Srinivas, D.; Gopinath, Chinnakonda S.; Ramaswamy, Veda (Acta Materialia, 2008)
Nano and microcrystalline, Mn/CeO2 solid solutions (5 mol.% Mn) have been prepared by solution combustion synthesis using urea, glycine or polyethylene glycol (PEG) as fuel. The nature of the fuel and its concentration (fuel to metal mole ratio, F/M have a strong influence on the physical and chemical characteristics of the resulting Mn/CeO2 solid solutions. The variations in the physicochemical properties are attributed to differences in (i) the adiabatic/real flame temperature realized with these fuels at different F/M ratios; (ii) the sustenance of the temperature or the quenching effect of the fuel at higher F/M ratios; (iii) combustion or decomposition of the precursors as the main course of the reaction; and (iv) the generation of gaseous products during combustion. Since the addition of the fuel to the initial precursor solution does not change the pH of the medium, the differences in the type of Mn species formed are mainly attributed to the combustion process. (C) 2007 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Keywords: Combustion synthesis; Mn-ceria; Nanocomposites; X-ray diffraction (XRD); X-ray photoelectron spectroscopy (XPS)

Electronic decoupling of surface layers from bulk and its influence in oxidation catalysis: a molecular beam study - Thirunavukkarasu, Kandasamy; Nagarajan, Sankaranarayanan; Gopinath, Chinnakonda S. (Applied Surface Science, 2009)
Interactions between oxygen and Pd-surfaces have important implications, especially towards oxidation reactions, and influence of subsurface oxygen to oxidation reactions is the focus of the present study. In our efforts to understand the above aspects, CO oxidation reactions have been carried out with mixed molecular beam (MB), consisting CO and O(2), on Pd(1 1 1) surfaces under a wide variety of conditions (T = 400-900 K, CO: O(2) = 7: 1 to 1: 10). A new aspect of the above reaction observed in the transient kinetics regime is the evidence for oxygen diffusion into Pd subsurface layers, and its significant influence towards CO oxidation at high temperatures (>= 600 K). Interesting information derived from the above studies is the necessity to fill up the subsurface layers with oxygen atoms to a threshold coverage (theta(O-sub)), above which the reactive CO adsorption occurs on the surface and simultaneous CO(2) production begins. There is also a significant time delay (G) observed between the onset of oxygen adsorption and CO adsorption (and CO(2) production). Above studies suggest an electronic decoupling of oxygen covered surface and subsurface layers, which is slightly oxidized, from the metallic bulk, which induces CO adsorption at high temperatures and simultaneous oxidation to CO(2). (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Electronic decoupling; heterogeneous catalysis; molecular beam; Oxidation; Pd(111); Subsurface diffusion

Electronic structure and catalytic study of solid solution of GaN in ZnO - Mapa, Maitri; Thushara, K. S.; Saha, Biswajit; Chakraborty, Purushottam; Janet, C. M.; Viswanath, R. P.; Nair, C. Madhavan; Murty, K. V. G. K.; Gopinath, Chinnakonda S. (Chemistry of Materials, 2009)
Solid solutions of GaN in ZnO (Zn1-zGaz)(O1-xNx) (x and z <= 0.15) have been prepared by simple solution combustion method, Except for minor changes in the lattice contraction, no significant change in the Wurtzite structure was observed. Raman and secondary ion mass spectrometry results show the direct Zn-N and Ga-N bonds in (Zn1-zGaz)(O1-xNx). Visible light absorption and XPS results demonstrate that N 2p states of nitride occupy the states above the O 2p valence band, and hence a change in optical band gap reduction occurs to similar to 2.5 eV from 3.37 eV for ZnO. Significant nitrogen fixation catalytic activity through NH3 formation has been observed at ambient pressure oil virgin (Zn1-zGaz)(O1-xNx) material, indicating its potential as a catalyst.

Evidence of cationic Pt active for water-gas shift reaction: Pt-doped BaCeO3 perovskite - Rajesh, Thattarathody; Rajarajan, Anakot K.; Gopinath, Chinnakonda S.; Devi, R. Nandini (Journal of Physical Chemistry C, 2012)
Precious metal incorporated into stable lattices like perovskites can be envisaged as an alternative catalysts to address deactivation problems. Here we report the barium cerate perovskite doped with varying amounts of Pt as catalysts for the water-gas shift reaction whereby ionic Pt is evidenced to be active. It is found that maximum CO conversion occurs above 325 degrees C and increases more than 2-fold after the first cycle. XPS analysis shows that after the first cycle, more ionic Pt species are present on the surface of the catalyst. X-ray and neutron diffraction studies also indicate the presence of oxygen vacancies that increases with increasing Pt substitution.

Effect of method of preparation on hydrodesulphurization activity of Co- or Ni-promoted MoS2/SBA-15 catalysts - Garg, Shelu; Soni, Kapil; Prasad, V. V. D. N.; Kumar, Manoj; Bhaskar, Thallada; Gupta, J. K.; Dhar, G. Murali; Gopinath, Chinnakonda S. (Journal of Chemical Sciences, 2014)
Ordered mesoporous material SBA-15 was synthesized and used as a support for the preparation of molybdenum sulphide catalysts through precipitation from homogeneous solution (PFHS) technique with the Mo content varying from 2-12 wt%. The prepared catalysts were evaluated for thiophene hydrodesulphurizadon catalytic activities at 400 degrees C. Catalysts prepared through PFHS method resulted in highly dispersed MoS2 catalysts, which were inferred from powder X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), low temperature oxygen chemisorptions (LTOC) and BET surface area analysis. The relationship between XPS intensity ratio, oxygen chemisorption and catalytic activities is discussed in terms of highly dispersed nano particles of MoS2 and its consequence in accommodating more promoted atoms at the edge sites.
Keywords: HDS; MoS2; PFHS method; promotional effects; SBA-15

Electronic structure-sunlight driven water splitting activity correlation of (Zn1-yGay)(O1-zNz) - Rajaambal, Sivaraman; Yadav, A. K.; Jha, Shambhu Nath; Bhattacharyya, Dibyendu; Gopinath, Chinnakonda S. (Physical Chemistry Chemical Physics, 2014)
(Zn1-yGay)(O1-zNz) (y <= 0.10; z <= 0.15) solid solutions have been investigated for their electronic structure and visible light photocatalytic activity, and a correlation was found between them. (Zn1-yGay)(O1-zNz) with ZnO as the major component have been synthesized by a solution combustion method in 10 minutes using simple raw materials. The local structures of Zn K edge and Ga K edge, and changes in the chemical environment with the incorporation of Ga and N in ZnO were determined by EXAFS study. EXAFS and XRD results suggested the dissolution of GaN in the ZnO lattice. The homogeneity of the solid solution was demonstrated from HRTEM studies. Photoluminescence studies revealed the creation of a new band at the top of the ZnO valence band (VB), and thus the broadening of the VB of (Zn1-yGay)(O1-zNz) or a decrease in the band gap was attributed to the origin of visible light absorption. UV-Vis spectral studies showed light absorption up to 550 nm, which directly supports the VB broadening. Predominant oxygen vacancies and high photocorrosion observed for ZnO were fully suppressed for (Zn1-yGay)(O1-zNz) , indicating the minimization of defects, and thus more sustainability under irradiation conditions. The bare solid solution exhibited reasonable and promising activity for solar hydrogen evolution and photoelectrochemical current generation at 0 V. The present work explained factors such as the preparation method, single phase structure with the stabilization of integral parts, homogeneity in the structure, compensation of oxygen vacancies, and suppression of the density of recombination centres that play a pivotal role in realizing solar energy harvesting.

Efficient Ag-nanoparticle embedded semi-IPN hydrogel for catalytic applications - Patwadkar, Manjusha V.; Gopinath, Chinnakonda S.; Badiger, Manohar V. (RSC Advances, 2015)
Silver nanoparticle embedded semi-IPN hydrogels based on a combination of poly(acrylamide) and poly(aspartic acid) were synthesized. These semi-IPN hydrogel networks can potentially serve as micro or nano reactors for entrapment of metal nanoparticles. Current methodology allows us to entrap metal nanoparticles throughout hydrogel networks via poly(aspartic acid) chains which are dispersed homogeneously in the gel matrix. The Ag-NPs were characterized by UV-vis absorption spectroscopy, transmission electronic microscopy (TEM), X-ray diffraction (XRD) and energy dispersive X-ray analysis (EDAX). The Ag embedded hydrogels catalyze the reduction of 4-nitrophenol to 4-aminophenol in the presence of NaBH4 very efficiently at room temperature with good recyclability upto 3 cycles.

Effective and selective oxidation of 2-butanol over Mn supported catalyst systems - Prabu, Kandasamy; Prabu, Marimuthu; Venugopal, Ashok Kumar; Venugopalan, Aswathy Thareparambil; Sandilya, W. V. Y. Sai; Gopinath, Chinnakonda S.; Raja, Thirumalaiswamy (Applied Catalysis A-General, 2016)
Oxidation of alcohols to their corresponding aldehydes/ketones is an important reaction in industries as well as in academic perspective. Selective oxidation (Selox) of alcohols like methanol, ethanol and propanol are well studied in literature; however, alcohols like butanol, pentanol, octanol is a challenging task. Selective oxidation of 2-butanol to methyl ethyl ketone (MEK) is an important reaction due to its wide range of applications. Herein, we demonstrated the selective oxidation of 2-butanol to MEK over Mn supported on different oxide supports. A series of MnxOy-Al2O3 (MA), MnxOy-CeO2 (MC), MnxOy-ZrO2 (MZ) and MnxOy-SiO2 (MS) catalysts were prepared by co-precipitation followed by hydrothermal method. As synthesised catalysts were characterised by various physico-chemical characterisation techniques. It was found that the presence of Mn3O4 species in MA and MZ catalysts is responsible for maximum catalytic activity towards 2-butanol oxidation. MA catalyst conferred a maximum 2-butanol conversion of 51% and 88% selectivity towards MEK. XPS analysis revealed that Mn in MA catalyst exists in +2 and +3 oxidation states and responsible for 2-butanol oxidation. Moreover it was found that the acidity of the catalyst also plays an important role in catalytic activity. (C) 2016 Published by Elsevier B.V.

Enhancement in rate of photocatalysis upon catalyst recycling - Sorathiya, Kalpesh; Mishra, Biswajit; Kalarikkal, Abhishek; Reddy, Kasala Prabhakar; Gopinath, Chinnakonda S.; Khushalani, Deepa (Scientific Reports, 2016)
Recyclability is an important aspect for heterogeneous photo-catalysts. Ease of recovery and stability of the photo-catalyst in terms of efficiency over the number of cycles are highly desired and in fact it is ideal if the efficiency is constant and it should not decrease marginally with each cycle. Presented here is a seminal observation in which the photocatalytic activity is shown to improve with increasing number of catalytic cycles (it is 1.7 times better after the 1st cycle and 3.1 times better after the 2nd cycle). Specifically, nanorods of pure TiO2 and TiO2 doped with controlled amount of tungsten have been used to degrade two model pollutants: Phenol and Rhodamine B under exclusive visible light illumination. It was found that, in case of 1 mol.% W incorporation, rate of photocatalysis and also the range of visible light absorption of the photocatalyst increased after the photocatalysis as compared to before photocatalysis. This aspect is unique for doped TiO2 and hence provides an intriguing way to mitigate low photoactivity.

Exploration of magnetically separable Ag@AgxNiy core/graded-alloy-shell nanostructures - Kumar, Mukesh; Soni, Kiran; Satpati, Biswarup; Gopinath, Chinnakonda S.; Deka, Sasanka (Chemical Communications, 2016)
We report novel bimetallic Ag@AgxNiy core@graded-alloy-shell nanoparticles (CGAS NPs), i.e. single Ag core NPs shelled by an AgxNiy graded alloy and stabilized by the CTAB surfactant employing a novel synthesis method. These Ag@AgxNiy CGAS NPs demonstrated superior catalytic performance in the synthesis of biologically active 3-amino alkylated indoles under green conditions.

Efficient organic photovoltaics with improved charge extraction and high short-circuit current - Mohan, Minu; Nandal, Vikas; Paramadam, Sanish; Reddy, Kasala Prabhakar; Ramkumar, Sekar; Agarwal, Sumanshu; Gopinath, Chinnakonda S.; Nair, Pradeep R.; Namboothiry, Manoj A. G. (Journal of Physical Chemistry C, 2017)
Exciton generation, dissociation, free carrier transport, and charge extraction play an important role in the short-circuit current (J(sc)) and power conversion efficiency of an organic bulk heterojunction (BHJ) solar cell (SC). Here we study the impact of band offset at the interfacial layer and the morphology of active layer on the extraction of free carriers. The effects are evaluated on an inverted BHJ SC using zinc oxide (ZnO) as a buffer layer, prepared via two different methods: ZnO nanoparticle dispersed in mixed solvents (ZnO A) and sol-gel method (ZnO B). The device with ZnO A buffer layer improves the charge extraction and J(sc),. The improvement is due to the better band offset and morphology of the blend near the ZnO A/active layer interface. Further, the numerical analysis of current-voltage characteristics illustrates that the morphology at the ZnO A/active layer interface has a more dominant role in improving the performance of the organic photovoltaic than the band offset.

Enhanced microwave absorption property of reduced graphene oxide (RGO)-strontium hexaferrite (SF)/poly (vinylidene) fluoride (PVDF) - Acharya, Sanghamitra; Gopinath, Chinnakonda S.; Alegaonkar, Prashant; Datar, Suwarna (Dimond and Related Materials, 2018)
Enormous growth in the use of electronic gadgets presents a challenge to develop efficient electromagnetic interference (EMI) shielding materials specifically using composites with properties such as light weight and high shielding due to absorption. In the present work we have synthesized a composite material with three components; Reduced Graphene Oxide (RGO) and Strontium Hexaferrite (SrFe12O19) (SF) bound together by polymer Poly (Vinylidene) Fluoride (PVDF). Composite RGO/SF (RGOSF) was prepared by facile one port chemical reduction method. Surface anchoring of similar to 500 nm of magnetic particles over the graphene sheet was confirmed by Field Emission Scanning Electron Microscopy (FESEM) and Transmission Electron Microscopy (TEM). Crystal structure of SF particles was analyzed before and after composite formation with RGO. Effective crystallite size was estimated from both XRD and Raman Spectroscopy which showed similar trend moving from SF to RGOSF to RGOSFPVDF. Polymer composite films of RGOSFPVDF were prepared by hot pressing. Both real and imaginary part of magnetic and dielectric parameters were studied. It was observed that enhancement of interfacial polarization and anisotropic heat loss in PVDF matrix was generated by RGOSF which ultimately created more scattering center and helped in absorption of electromagnetic radiation. Critical film thickness of 3 mm was capable to shield up to 33 dB EM energy of which > 99.9% was due to absorption.

Electronic integration and thin film aspects of Au-Pd/rGO/TiO2 for improved solar hydrogen generation - Tudu, Bijoy; Nalajala, Naresh; Reddy, Kasala P.; Saikia, Pranjal; Gopinath, Chinnakonda S. (ACS Applied Materials & Interfaces, 2019)
In the present work, we have synthesized noble bimetallic nanoparticles (Au-Pd NPs) on a carbon-based support and integrated with titania to obtain Au-Pd/C/TiO2 and Au-Pd/rGO/TiO2 nanocomposites using an ecofriendly hydrothermal method. Here, a 1:1 (w/w) Au-Pd bimetallic composition was dispersed on (a) high-surface-area (3000 m(2) g(-1)) activated carbon (Au-Pd/C), prepared from a locally available plant source (in Assam, India), and (b) reduced graphene oxide (rGO) (Au-Pd/rGO); subsequently, they were integrated with TiO2. The shift observed in Raman spectroscopy demonstrates the electronic integration of the bimetal with titania. The photocatalytic activity of the above materials for the hydrogen evolution reaction was studied under 1 sun conditions using methanol as a sacrificial agent in a powder form. The photocatalysts were also employed to prepare a thin film by the drop-casting method. Au-Pd/rGO/TiO2 exhibits 43 times higher hydrogen (H-2) yield in the thin film form (21.50 mmol h(-1) g(-1)) compared to the powder form (0.50 mmol h(-1) g(-1)). On the other hand, Au-Pd/C/TiO2 shows 13 times higher hydrogen (H-2) yield in the thin film form (6.42 mmol h(-1) g(-1)) compared to the powder form (0.48 mmol h(-1) g(-1)). While powder forms of both catalysts show comparable activity, the Au-Pd/rGO/TiO2 thin film shows 3.4 times higher activity than that of Au-Pd/C/TiO2. This can be ascribed to (a) an effective separation of photogenerated electron-hole pairs at the interface of Au-Pd/rGO/TiO2 and (b) the better field effect due to plasmon resonance of the bimetal in the thin film form. The catalytic influence of the carbon-based support is highly pronounced due to synergistic binding interaction of bimetallic nanoparticles. Further, a large amount of hydrogen evolution in the film form with both catalysts (Au-Pd/C/TiO2 and Au-Pd/rGO/TiO2) reiterates that charge utilization should be better compared to that in powder catalysts.
Keywords: bimetal; Photocatalysis; surface plasmon resonance; TiO2; water splitting

Electronic structure evolution of Pd@Co nanocatalysts under oxidation and reduction conditions and preferential CO oxidation - Jain, Ruchi; Gopinath, Chinnakonda S. (ChemCatChem, 2020)
Herein, we present the surface electronic structure and morphological evolution under reduction and oxidation conditions for Pd@Co (PC) core-shell nanoparticles with different Pd : Co ratio (PC=2 : 1, 1 : 1 and 1 : 2). Extensive measurements have been made with NAPXPS (near ambient pressure x-ray photoelectron spectroscopy) under oxidising and reducing conditions, and ex-situ HRTEM. It has been demonstrated that PC catalysts are thermally stable towards morphological changes, at least up to 575 K. Nonetheless, it shows a significant surface electronic structure changes under reaction environments, which are highly relevant to heterogeneous catalysis. As expected, high (low) population of metallic (oxidised) Co was observed, while retaining core shell structure under reduction (H(2)and vacuum annealing) environment. Interestingly, the Pd-Co metallic interface helps to overcome the pyrophoric nature of cobalt and stabilised a significant amount of metallic Co at Pd-Co interface even in the presence of 0.1 mbar O(2)up to 575 K. The presence of Pd-Co and Pd-Co@Co(3)O(4)interfaces in reaction environment makes the catalyst dual functional. The proof of concept has been explored in terms of oxidation of CO in the presence of H(2)or O-2.
Keywords: Core-Shell morphology; Electronic Structure; heterogeneous catalysis; interface; XPS

Electronically integrated mesoporous Ag-TiO2 nanocomposite thin films for efficient solar hydrogen production in direct sunlight - Mani, Sunesh S.; Rajendran, Sivaraj; Nalajala, Naresh; Mathew, Thomas; Gopinath, Chinnakonda S. (Energy Technology, 2021)
The synthesis of mesoporous TiO2 by a solution-based assembly process and Ag/TiO2 nanocomposites is provided. The efficacy of Ag/TiO2 nanocomposite as photocatalyst in thin-film form is demonstrated for solar hydrogen generation in sunlight. Integration of Ag with TiO2 dramatically enhanced the H-2 production: with 1 wt% Ag on TiO2 (TiAg-1), the H-2 yield was observed to be 4.59 mmol h(-1) g(-1), which is 2.3 (30) times larger than 0.5 wt% Ag on TiO2. TiAg-1 shows 4.3 times higher activity in film form compared with its powder counterpart. High photocatalytic efficiency is attributed to the surface plasmon resonance effect of Ag, electronic integration of Ag with TiO2, and subsequent valence band broadening, large distribution of Ag nanoparticles and abundant Ag-TiO2 Schottky junctions, and the later minimizes electron-hole recombination. Interparticle mesoporous network increases necking and the high surface area offers easy accessibility of the reactants to a large number of active sites.
Keywords: heterogeneous catalysis; heterojunctions; plasmon effect; Silver; solar energy conversion; Solar hydrogen

Electronic structure evolution from metallic vanadium to metallic VxOy: a nappes study for o2+v gas-solid interaction - Ranjan, Ravi; Mhamane, Nitin B.; Kolekar, Sadhu K.; Gopinath, Chinnakonda S. (Journal of Physical Chemistry C, 2022)
Gas-solid interactions between molecular oxygen and metallic vanadium surfaces and the systematic evolution in the electronic structure of vanadium oxide (VOx) surfaces have been explored in the present work by near-ambient pressure photo-electron spectroscopy (NAPPES). The current article studies the evolution of various oxides of vanadium as a function of partial pressure of O2 (ultrahigh vacuum to 1 mbar), temperature (298- 875 K), and the exposure time to oxygen (up to 18 h). Valence -band (VB) and core-level spectral measurements recorded with UV (He-I = 21.2 eV) and Al K alpha (1486.6 eV) photons, respectively, show interesting changes. (1) Oxidation is limited to the top layers of vanadium at 298 K and up to a partial pressure of 1 mbar O2. About 50% of vanadium gets oxidized, and the remaining amount exists as metal within the top 10 nm. (2) Metallic vanadium disappears above 625 K, and it is predominantly oxidized to a mixture of V4+ and V5+ oxidation states at a 0.1 mbar partial pressure of O2. Points 1 and 2 suggest the predominantly thermodynamically controlled nature of vanadium oxidation through oxygen diffusion into the subsurface and bulk layers. (3) The Fermi-level (EF) feature observed first at >= 725 K at a 0.1 mbar O2 pressure demonstrates the formation of metallic VO2; however, its metallic nature is preserved even at ambient temperature due to interweaving nanodomains of VOx with VO2. (4) Only partial conversion of surface layers to V5+ (V2O5) along with VO2 and V2O3 (within the probing depth of 8-10 nm by near-ambient pressure X-ray photoelectron spectroscopy (NAP-XPS)) was observed even after prolonged heating (18 h) in 1 mbar O2 pressure. (5) The nature of the surface changes between metal and semiconducting/ insulator oxides is substantiated by the observation of changes in work function (phi) and EF features. Typical VB features and Fermi intensity of V-metal and vanadium oxides were observed, and the results were corroborated with core-level and VB spectra. The present results extend the capabilities of NAPPES to explore the electronic structure evolution as a function of reaction conditions and underscore its relevance to areas such as heterogeneous catalysis and sensing.

Enhanced hydrogen fuel production using synergistic combination of solar radiation and TiO2 photocatalyst coupled with Burkholderia cepacia lipase - de Souza Brandao, Luma Mirely; Barbosa, Milson dos Santos; de Jesus, Roberta Anjos; Bharad, Pradnya Arunrao; Lima, Alvaro Silva; Faria Soares, Cleide Mara; Navarro Yerga, Rufino Manuel; Bilal, Muhammad; Romanholo Ferreira, Luiz Fernando; Iqbal, Hafiz M. N.; Gopinath, Chinnakonda S.; Figueiredo, Renan Tavares (International Journal of Hydrogen Energy, 2022)
Promising and sustainable alternatives for hydrogen production have been investigated. Among these, the use of enzymes may represent an efficient alternative. In this work, an increase in hydrogen production under simulated sunlight by combining TiO2 and TiO2/MgCl2 with Burkholderia cepacia lipase (BCL) was reported. The samples (TiO2, TiO2/MgCl2, and TiO2 /MgCl2/BCL) were characterized by X-ray diffraction (XRD), thermo-gravimetric (TGA), N-2 adsorption-desorption isotherms (BET), scanning electron microscopy (SEM), and UV-Visible absorption spectra. Hydrogen production tests were performed in aqueous methanol solutions under simulated sunlight. The results demonstrated that 130-times greater increase in hydrogen production rate was observed by the addition of BCL than individual TiO2. This better hydrogen production rate can be attributed to the increase in the amount of reduction equivalent of the system due to the oxidation of protein peptides caused by TiO2. In conclusion, the results indicate that hydrogen production efficiency can be significantly improved when integrating TiO2/MgCl2 with BCL. (C) 2022 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: hydrogen production; Lipase; Nano-conjugated enzymes; Photocatalyst; Solar radiation; Titanium dioxide

Electrocatalytic and selective oxidation of glycerol to formate on 2D 3d-metal phosphate nanosheets and carbon-negative hydrogen generation - Chauhan, Inderjeet; Vijay, Pothoppurathu M.; Ranjan, Ravi; Patra, Kshirodra Kumar; Gopinath, Chinnakonda S. (ACS Materials Au, 2024)
In the landscape of green hydrogen production, alkaline water electrolysis is a well-established, yet not-so-cost-effective, technique due to the high overpotential requirement for the oxygen evolution reaction (OER). A low-voltage approach is proposed to overcome not only the OER challenge by favorably oxidizing abundant feedstock molecules with an earth-abundant catalyst but also to reduce the energy input required for hydrogen production. This alternative process not only generates carbon-negative green H2 but also yields concurrent value-added products (VAPs), thereby maximizing economic advantages and transforming waste into valuable resources. The essence of this study lies in a novel electrocatalyst material. In the present study, unique and two-dimensional (2D) ultrathin nanosheet phosphates featuring first-row transition metals are synthesized by a one-step solvothermal method, and evaluated for the electrocatalytic glycerol oxidation reaction (GLYOR) in an alkaline medium and simultaneous H2 production. Co3(PO4)2 (CoP), Cu3(PO4)2 (CuP), and Ni3(PO4)2 (NiP) exhibit 2D sheet morphologies, while FePO4 (FeP) displays an entirely different snowflake-like morphology. The 2D nanosheet morphology provides a large surface area and a high density of active sites. As a GLYOR catalyst, CoP ultrathin (∼5 nm) nanosheets exhibit remarkably low onset potential at 1.12 V (vs RHE), outperforming that of NiP, FeP, and CuP around 1.25 V (vs RHE). CoP displays 82% selective formate production, indicating a superior capacity for C–C cleavage and concurrent oxidation; this property could be utilized to valorize larger molecules. CoP also exhibits highly sustainable electrochemical stability for a continuous 200 h GLYOR operation, yielding 6.5 L of H2 production with a 4 cm2 electrode and 98 ± 0.5% Faradaic efficiency. The present study advances our understanding of efficient GLYOR catalysts and underscores the potential of sustainable and economically viable green hydrogen production methodologies.

Electrocatalytic glycerol conversion: a low-voltage pathway to efficient carbon-negative green hydrogen and value-added chemical production - Chauhan, Inderjeet; Bajpai, Himanshu; Ray, Bishakha; Kolekar, Sadhu K.; Datar, Suwarna; Patra, Kshirodra Kumar; Gopinath, Chinnakonda S. (ACS Applied Materials and Interfaces, 2024)
Electrochemical glycerol oxidation reaction (GLYOR) could be a promising way to use the abundantly available glycerol for production of value-added chemicals and fuels. Completely avoiding the oxygen evolution reaction (OER) with GLYOR is an evolving strategy to reduce the overall cell potential and generate value-added chemicals and fuels on both the anode and cathode. We demonstrate the morphology-controlled palladium nanocrystals, afforded by colloidal chemistry, and their established morphology-dependent GLYOR performance. Although it is known that controlling the morphology of an electrocatalyst can modulate the activity and selectivity of the products, still it is a relatively underexplored area for many reactions, including GLYOR. Among nanocube (Pd-NC), truncated octahedron (Pd-TO), spherical and polycrystalline (Pd-PC) morphologies, the Pd-NC electrocatalyst deposited on a Ni foam exhibits the highest glycerol conversion (85%) along with 42% glyceric acid selectivity at a low applied potential of 0.6 V (vs reversible hydrogen electrode (RHE)) in 0.1 M glycerol and 1 M KOH at ambient temperature. Owing to the much favorable thermodynamics of GLYOR on the Pd-NC surface, the assembled electrolyzer requires an electricity input of only similar to 3.7 kWh/m(3) of H-2 at a current density of 100 mA/cm(2), in contrast to the requirement of >= 5 kWh/m(3) of H-2 with an alkaline/PEM electrolyzer. Sustainability has been successfully demonstrated at 10 and 50 mA/cm(2) and up to 120 h with GLYOR in water and simulated seawater.
Keywords: electrocatalysis; Glycerol; green hydrogen; nanocube; Palladium; SDG

The ex situ exsolved exsolved Ni-Ru alloy from nickel-ruthenium co-doped SrFeO perovskite as a potential catalyst for C=C and C=O hydrogenation - Bhavisha, Meloth; Balamurugan, Sarkarainadar; Gopinath, Chinnakonda S.; Sakthivel, Ayyamperumal (SUSTAINABLE ENERGY & FUELS, 2024)
Keywords: LIQUID-PHASE HYDROGENATION; OXIDE FUEL-CELLS

Exploring defect-engineered metal-organic frameworks with 1,2,4-triazolyl isophthalate and benzoate linkers - Chetry, Sibo; Lukman, Muhammad Fernadi; Bon, Volodymyr; Warias, Rico; Fuhrmann, Daniel; Moellmer, Jens; Belder, Detlev; Gopinath, Chinnakonda S.; Kaskel, Stefan; Poeppl, Andreas; Krautscheid, Harald (INORGANIC CHEMISTRY, 2024)
Keywords: Separation; spectroscopy; TRIAZOLYL

Efficient hydrogen liberation from autocatalytic wastewater treatment by green synthesized Ag2SeO3 nanocatalyst - Islam, Sk Najrul; Ansari, Ifra Ilyas; Gopinath, Chinnakonda S.; Ahmad, Absar (Inorganic Chemistry Communications, 2025)
Concerns about wastewater management, secure hydrogen storage, and interest in an affordable, effective, and user-friendly technique for releasing hydrogen have grown globally. Developing sustainable synthetic processes that result in industrially significant nanocatalyst to synergistically accelerate the evolution of hydrogen from wastewater treatment is extremely desirable. This work, for the first time, demonstrates the design and green fabrication of bactericidal silver selenite nanoparticles (Ag2SeO3 NPs) using the fungus Aspergillus niger for autocatalytic hydrogen production and methylene blue dye reduction by hydrolytic dehydrogenation of NaBH4. The morphology of Ag2SeO3 nanocatalysts with an average particle size of 60 nm was assessed by FETEM, while their surface chemistry, crystal structure, and optical properties were examined using XPS, XRD, and FTIR/ UV-Visible spectrophotometers, respectively. The sigmoidal trajectory of NaBH4 dehydrogenation with turnover frequencies (TOF) of 4750 mL g- 1 min- 1 suggested good autocatalytic activity of Ag2SeO3 NPs. The mechanistic study unveiled that autocatalysis was made possible by the creation of novel, active Ag co-catalyst which works synergistically with Ag2SeO3 NPs. For in-situ, real time assessment of Ag concentration during catalysis, hydrolysis of NaBH4 was carried out in the presence of methylene blue dye. The results showed that the active cocatalyst centers have a significant influence on autocatalytic hydrogen production at room temperature, reducing 98.8 % methylene blue (MB) dye in 6 min with a lesser hydrogen generation rate of 4174 mL g- 1 min- 1. The catalyst exhibited excellent stability and durability after fourth consecutive cycle, demonstrating its promise for long-term and recurring application in hydrogen liberation from autocatalytic MB dye reduction.
Keywords: Ag2SeO3 nanoparticles; Antibacterial; autocatalysis; Hydrogen generation; Wastewater treatment

Enhanced mid-visible light absorption and long-lived charge carriers in an electronically and structurally integrated BiVO4-TiO2 photoanode for efficient artificial photosynthesis applications - Jha, Vikas Kumar; Salgaonkar, Kranti N.; Saha, Avishek; Gopinath, Chinnakonda S.; Iyer, E. Siva Subramaniam (Nanoscale, 2025)
The ever-increasing demand for sustainable solutions for eliminating environmental pollutants, solar energy harvesting, water splitting, etc. have led to the design and development of novel materials to achieve the desired result. In this regard, structurally and electronically integrated (SEI) BiVO4-TiO2 (SEI-BVT) with abundant heterojunctions has emerged as a promising entity for efficient charge separation, which in turn enhances artificial photosynthesis (APS) activity. The present work adopted a unique synthetic strategy using SILAR to fabricate SEI-BVT from ionic precursors (Bi3+ and VO43-) into the pores of TiO2, exhibiting benchmark APS efficiency compared to the individual components. This preparation results in approximately 180 trillion uniformly distributed heterojunctions in 1 mg cm-2 of the SEI-BVT photoanode material. Charge carriers in SEI-BVT and BiVO4 are similar; however, the recombination is highly hindered when SEI-BVT heterojunctions are formed in the former. Our earlier work demonstrated 31-38% solar-to-fuel efficiency (STFE) with BiVO4-TiO2 for APS in the presence of the Pd-nanocube co-catalyst. The emphasis of the current work is to explore the dynamics of the light-induced processes in these heterojunctions to understand the interfacial charge transfer process. Femtosecond transient absorption (TA) spectroscopy has been employed to monitor the excited state dynamics. Our results show that new trap states have evolved under light illumination, which are significantly long-lived and hinder charge recombination, and consequently enhance STFE. A significantly large number of charge carriers exhibit a lifetime of >> 6 ns with visible light photons, at least up to 720 nm, which is higher than the band-gap absorption onset at 490 nm for SEI-BVT compared to bulk BiVO4. The rate of formation of charge carriers is significantly affected in the heterojunctions.

Europium oxide on carbon nitride for electrocatalytic glycerol oxidation coupled with hydrogen evolution reaction - Jana, Jayasmita; Sharma, Tata Sanjay Kanna; Ghanem, Mohamed A.; Choi, Won Mook; Gopinath, Chinnakonda S.; Hur, Seung Hyun (Separation and Purification Technology, 2025)
{The integration of the electrochemical glycerol oxidation reaction (GOR) with the hydrogen evolution reaction (HER) has emerged as a promising alternative to the sluggish oxygen evolution reaction (OER) in water splitting toward the development of renewable and clean energy sources. However, suitable electrodes that facilitate redox kinetics while increasing the selectivity of the desired product(s) are still required. Herein, a series of europium oxide (Eu2O3) anchored on graphitic carbon nitride (g-CN) nanoaggregates (g-CNEux
Keywords: carbon support; electrocatalysis; Glycerol; HER; Rare earth metal